Mitral regurgitation impact on left atrial myopathy in hypertrophic cardiomyopathy. Issue 6 (29th May 2022) - Zegkos, Thomas; Kamperidis, Vasileios; Gossios, Thomas; Ntelios, Dimitris; Parcharidou, Despoina; Papanastasiou, Christos A.; Panagiotidis, Theofilos; Tsianaka, Theodora; Rouskas, Pavlos; Katranas, Sotiris; Karvounis, Haralambos; Efthimiadis, Georgios
Abstract: Background: : Recent studies have shown that mitral regurgitation (MR) represents a major determinant of left atrial (LA) function in patients with heart failure with preserved ejection fraction. The role of MR in determining LA myopathy in hypertrophic cardiomyopathy (HCM) is unknown. The aim of this study was to examine the association of MR with LA myopathy, assessed by LA strain values in HCM patients. Methods: : In total 250 consecutive patients (mean age 51 ± 16 years, 67.2% male) with an established diagnosis of HCM and with sinus rhythm at index echocardiography evaluation were included. LA reservoir, conduit and booster strain were analyzed, besides LA size, left ventricular (LV) systolic and diastolic function. The predictors of LA strain values were identified with linear regression analysis. Results: : Significant (more than mild) MR was a significant univariate predictor of all the three LA strain values. In multivariate linear regression analysis, independent predictors of LA reservoir strain were more than mild MR (r = −.23), LV global longitudinal strain (r = −.49), LA volume index (r = −.27) and patient age (r = −.23). Significant MR was also an independent determinant of LA conduit (r = −.17) and booster strain (r = −.12). In patients with LA volume index < 34 ml/m 2 more than mild MR was an independent predictor of LA reservoir (r = −.32) and conduit strain (r = −.27), but not LA booster strain. Conclusion: : Significant MR is associated with LA myopathy independently of the LV diastolic and systolic function and LA size.